Tinjauan Kapasitas dan Detailing Lentur Dan Geser Balok Beton Bertulang Konvensional Berdasarkan SNI 2847:2013 Dengan Pertimbangan Aspek Kemudahan Praktik Di Lapangan dan Acuan Rules Of Thumb Studio Arsitektur - Yudhiarma Yudhiarma; Herry Prabowo; Mochammad Hilmy (Politeknik Negeri Pontianak, 2021)
The main parameters that determine the flexural and shear capacity of a reinforced concrete beam include the dimensions of the beam, the quality of the concrete, the quality of steel reinforcement, the size of steel reinforcement, and the amount of steel used. In practice, these parameters generally have a certain value so that for certain spans, also the details of a reinforced concrete stress block, can be estimated by taking parameters that exist in the field as constraints. The process of drawing and estimating detailed beams in an studio of architecture usually also refers to practical needs in the field. So by providing limits on span, concrete quality, and steel quality, a drafter can estimate the details of the beam under review. The process of calculating beam dimensions is done by estimating the cross section height of the beam (h) and the width of the beam (b) according to the ‘Rules of Thumb“ reference. The dimension calculation based on effective beam span 4m, 5m, 6m, 7m, and 8m produces the smallest beam dimension, namely B20/35 beam and the largest is B55 / 80..